Efficient Photodynamic Therapy on Human Retinoblastoma Cell Lines - Walther, Jan (Public Library of Science, 2014)
Photodynamic therapy (PDT) has shown to be a promising technique to treat various forms of malignant neoplasia. The photodynamic eradication of the tumor cells is achieved by applying a photosensitizer either locally or systemically and following local activation through irradiation of the tumor mass with light of a specific wavelength after a certain time of incubation. Due to preferential accumulation of the photosensitizer in tumor cells, this procedure allows a selective inactivation of the malignant tumor while sparing the surrounding tissue to the greatest extent. These features and requirements make the PDT an attractive therapeutic option for the treatment of retinoblastoma, especially when surgical enucleation is a curative option. This extreme solution is still in use in case of tumours that are resistant to conventional chemotherapy or handled too late due to poor access to medical care in less advanced country. In this study we initially conducted in-vitro investigations of the new cationic water-soluble photo sensitizer tetrahydroporphyrin-tetratosylat (THPTS) regarding its photodynamic effect on human Rb-1 and Y79 retinoblastoma cells. We were able to show, that neither the incubation with THPTS without following illumination, nor the sole illumination showed a considerable effect on the proliferation of the retinoblastoma cells, whereas the incubation with THPTS combined with following illumination led to a maximal cytotoxic effect on the tumor cells. Moreover the phototoxicity was lower in normal primary cells from retinal pigmented epithelium demonstrating a higher phototoxic effect of THPTS in cancer cells than in this normal retinal cell type. The results at hand form an encouraging foundation for further in-vivo studies on the therapeutic potential of this promising photosensitizer for the eyeball and vision preserving as well as potentially curative therapy of retinoblastoma.